Molecular phylogeny of the butterfly genus Polytremis (Hesperiidae, Hesperiinae, Baorini) in China. - Weibin Jiang; Jianqing Zhu; Chao Song; Xiaoyan Li; Yue Yang; Weidong Yu (PLoS ONE, 2013)
BACKGROUND: The genus Polytremis, restricted to the continental part of the southeastern Palaearctic and northern Oriental regions, is one of the largest and most diverse lineages of the tribe Baorini. Previous studies on the genus were focused mainly on morphological classification and identification of new species. Due to the lack of effective and homologous traits of morphology, there were many challenges in the traditional classification. In this report, we reconstruct the phylogeny to provide a solid framework for these studies and to test the traditional limits and relationships of taxa. METHODOLOGY AND PRINCIPAL FINDINGS: We sequenced a mitochondrial and three nuclear gene fragments, coupled with an evaluation of traditional morphological characters, to determine the phylogenetic relationships for a total of 15 species representing all major species groups of the Polytremis genus in China, and to elucidate their taxonomic status. CONCLUSIONS AND SIGNIFICANCE: Analysis of mitochrondial and nuclear DNA showed considerable congruent phylogenetic signal in topology at the inter-species level. We found strong support for the monophyly of Polytremis and some clades were recognized with morphological data. Thus, the COI sequence in our study could be used as a DNA barcode to identify almost all members of the genus. However, incongruences of phylogenetic analyses occurred: in contrast to the phylogenetic trees of mitochondrial COI, it was not possible for nuclear rDNA to discriminate P. gotama from P. caerulescens, suggesting a possible recent separation of these two species. Additionally, P. theca was the only species with a greater intra-specific genetic distance compared to some inter-specific genetic distances in this study and some problems associated with the cryptic diversity of the species are discussed. The results of this study will helpful to reveal the causes of the high degree of diversity of butterflies, and possibly other groups of insects in China.